THE EFFECT OF GOOD CORPORATE GOVERNANCE, ESG DISCLOSURE, AND GREEN INNOVATION ON FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES FOR THE PERIOD 2021-2024 (A STUDY OF THE BASIC INDUSTRY AND CHEMICAL SUB-SECTORS ON THE INDONESIA STOCK EXCHANGE) - Nabila Ramadhanty A; Nur Ravita Hanun (Antis Publisher, 2025)
Objective: This study aims to determine the effect of GCG, ESG Disclosure, and Green Innovation on Financial Performance (ROA). Method: This study uses a quantitative method. The research subjects are companies in the basic and chemical industry sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The sampling technique used was purposive sampling, resulting in 34 companies that met the criteria. The analysis technique used in this study was multiple linear regression. Results: The results of the study show that: (1) GCG, proxied by an independent board of commissioners, has no effect on financial performance, (2) ESG Disclosure has an effect on financial performance, (3) Green Innovation has no effect on financial performance in companies in the basic and chemical industry sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. Novelty: The study identifies how GCG, ESG Disclosure, and Green Innovation differently influence financial performance within the basic and chemical industry sub-sector in Indonesia, showing that ESG Disclosure uniquely affects financial performance while GCG and Green Innovation do not.